2012
DOI: 10.1016/j.jacc.2012.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA-34a Contributes to the Impaired Function of Bone Marrow-Derived Mononuclear Cells From Patients With Cardiovascular Disease

Abstract: These results demonstrate that cardiovascular disease modulates the miR expression of BMCs in humans. Reducing the expression of the pro-apoptotic miR-34a improves the survival of BMCs in vitro and enhances the therapeutic benefit of cell therapy in mice after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 42 publications
0
64
0
Order By: Relevance
“…93,94 Jakob et al 95 reported that peripheral blood-derived CD34 + stem cells and early outgrowth cells have significantly reduced the levels of proangiogenic miRNA-126 and miR-130a in patients with chronic heart failure caused by ischemic cardiomyopathy as compared with healthy subjects. Other reports in mouse models suggest that cardiac ischemia mobilizes BM mononuclear cells via downregulating the expression of miR-150 activating CXCR4 in BM mononuclear cells.…”
Section: Exosomal Mirnas Reprogramming the Bmmentioning
confidence: 99%
“…93,94 Jakob et al 95 reported that peripheral blood-derived CD34 + stem cells and early outgrowth cells have significantly reduced the levels of proangiogenic miRNA-126 and miR-130a in patients with chronic heart failure caused by ischemic cardiomyopathy as compared with healthy subjects. Other reports in mouse models suggest that cardiac ischemia mobilizes BM mononuclear cells via downregulating the expression of miR-150 activating CXCR4 in BM mononuclear cells.…”
Section: Exosomal Mirnas Reprogramming the Bmmentioning
confidence: 99%
“…Xu et al found that bone marrow cells isolated from MI patients display increased miR-210 and miR-34a levels (148). The latter appears as particularly important for this cell type: inhibition of miR-34 significantly decreases hydrogen peroxideinduced cell death in vitro, whereas its overexpression reduces the bone marrow cell survival.…”
Section: Stem Cells For MI Therapy and Hypoxamirmentioning
confidence: 99%
“…In fact, its overexpression induces senescence in pro-angiogenic cultured endothelial progenitor cells, 41 and promotes cell death in bone marrow-derived pro-angiogenic cells. 42 Mir-34 is induced by p53, even though its levels can also be increased independently of p53. 42, 43 Important miR-34 targets include SIRT1, Bcl-2 and other cell cycle regulators.…”
mentioning
confidence: 96%